CO2 absorption of anhydrous colloidal suspension based silica nanospheres with different microstructures. Issue 8 (December 2021) - Ding, Yudong; Guo, Liheng; Li, Xiaoqiang; Liao, Qiang; Zhu, Xun; Wang, Hong
Liquid absorption and solid adsorption technologies have been researched and reported widely for CO2 capture. Combining the advantages of these two capture materials, a novel anhydrous colloidal suspension was synthesized by dispersing amine-modified microporous silica nanospheres in 2-[2-(dimethylamino) ethoxy] ethanol. In this study, solid, hollow, and porous silica nanospheres with different internal pore structures were synthesized and characterized. The effects of the silica nanosphere microstructures on diethylenetriamine loading and CO2 absorption in anhydrous colloidal suspensions were studied. Due to a more developed pore structure, the hollow and porous silica-based absorbents possessed stronger amine loading capacities compared to solid silicon-based absorbent, and the best absorption performance was an absorption capacity of 1.2543 mmol/g at a pressure of 150 kPa and a temperature of 300 K. The results indicated that pore structure had a significant influence on the absorption property, and the porous silica-based absorbent was more favorable for CO2 absorption than solid and hollow silica-based absorbents. Moreover, the pseudo-second-order model was successful in predicting the CO2 absorption process in colloidal suspensions.